Gastrointestinal complications of the Ehlers-Danlos syndrome. Issue 12 (December 1969) - Beighton, Peter H.; Murdoch, J. Lamont; Votteler, Theodore
Abstract : The gastrointestinal abnormalities encountered in 125 patients with the Ehlers-Danlos syndrome have been described. Spontaneous perforation of the intestine and massive gastrointestinal haemorrhage are uncommon but potentially lethal complications of the Ehlers-Danlos syndrome. Less dangerous abnormalities, such `as external hernia, hiatus hernia, eventration of the diaphragm, intestinal diverticula, and rectal prolapse were all encountered in patients in the series. Abdominal surgery in affected patients may be made difficult by fragility of tissues and a bleeding tendency. In the postoperative period, tearing out of sutures and wound dehiscence may occur.